Machiavelli's gospel the critique of Christianity in The prince - Parsons, William 1976- (University of Rochester Press, 2016)
Recent scholarship on The Prince interprets the classic work in the context of Machiavelli's sixteenth-century Italy, but this scholarship neglects the source on which the moral and political world of the sixteenth century was based, the Christian Bible. In this study of The Prince, William Parsons plumbs Machiavelli's allusions to the Bible, along with his statements on the church,and shows that Machiavelli was a careful reader of the Bible and an astute observer of the church. Machiavelli's teaching in The Prince, Parsons contends, might be instructively compared with that of the church's teacher, Jesus Christ. Parsons undertakes what recent interpreters of The Prince have not done: contrast Machiavelli's advice with the teachings of Christ. The result is a new reading of The Prince, revealing in Machiavelli's political thought a systematic critique of the teachings of the New Testament and its model for human life, Christ. In this study of the one of greatest works on politics ever written, Parsons not only challenges the most recent interpretations of The Prince but also gives new understanding to the reading that made Machiavelli famous. William Parsons is associate professor of political science at Carroll College
Title from publisher's bibliographic system (viewed on 04 Jun 2021)
Ntroduction : Christianity, Christ, and Machiavelli's The prince -- Christianity's siren song -- Christ's defective political foundations -- Hope is not enough -- The prince of war -- Machiavelli's unchristian virtue -- Christ's ruinous political legacy -- The harrowing redemption of Italy -- Conclusion : Machiavelli's gospel
Keywords: Machiavelli, Niccolò / 1469-1527 / Principe; Jesus Christ / In literature; Machiavelli, Niccolò -- 1469-1527 -- Il principe; Christianity and politics; Christentum; Kommentar